Effect of core training on skill performance among athletes: A systematic review - Lou, S.; Soh, K. G.; Soh, K. L.; Sun, H.; Modh Nasiruddin, N. J.; Du, C.; Zhai, X. (Frontiers in Physiology, 2022)
Background: This study aims to present a critical review of the existing literature on the effect of core training on athletes` skill performance, and to provide recommendations and suggest future research directions for both coaches and researchers.